Sustainable Evolution: Investigating the Factors Contributing to the Transformation of Coffee Businesses from Unplanned to Well-Planned, Sustainable Enterprises in Padang - Riswanto, Habib Adani; Maruf, Maruf; Syafrizal, Syafrizal (Graduate Program Magister Manajemen Pendidikan, 2024)
This research aims to identify the factors contributing to the sustainable evolution of coffee businesses in Padang, West Sumatra. The research is an exploratory qualitative study. Each coffee shop, while differing in focus and approach, prioritizes quality, utilizes technology, and implements strategies for long-term sustainability in its operations. Each coffee shop demonstrates unique strategies in outbound logistics, whether through distribution methods, technology integration, strategic cooperation, or customer engagement, tailored to its specific business model and target audience. Each coffee shop employs unique marketing and sales strategies tailored to its business model and target audience, emphasizing customer engagement, promotional diversity, and long-term relationship building. Each coffee shop offers unique services, focusing on customer experience, atmosphere, personalized interactions, and proactive issue resolution to build strong customer relationships and foster loyalty. Each coffee shop employs distinct procurement strategies tailored to its business model and goals, focusing on supplier relationships, diversification, and preparedness for uncertainties to ensure smooth operations and long-term sustainability. Each coffee shop employs structured mentoring, technology integration, and maintenance practices tailored to support long-term sustainability and business growth, ensuring efficient operations and a positive environmental and community impact. Each coffee shop employs structured recruitment, training, and development programs tailored to their business needs, emphasizing employee skill enhancement, performance improvement, and continuous learning to provide excellent service. Each coffee shop employs technology as a tool to enhance sustainability, efficiency, and productivity, utilizing strategies tailored to their specific needs and challenges, whether it’s overcoming network interference, ensuring reliable technology selection, or managing repair costs efficiently.